2018
DOI: 10.1259/bjr.20180259
|View full text |Cite
|
Sign up to set email alerts
|

Imaging peritoneal metastasis of gastric cancer with 18F-fluorothymidine positron emission tomography/computed tomography: a proof-of-concept study

Abstract: This proof-of-concept study shows that [F-18]FLT-PET/CT is a sensitive method for detecting PM in GC, and paves the way for future studies investigating the clinical utility of this approach for the detection of clinically non-evident PM in GC. Advances in knowledge: This proof-of-concept study found that [F-18]FLT-PET/CT is a sensitive method for detecting peritoneal metastases in GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…A systematic review by Riola-Parada et al [8] showed that PET/MRI was superior or similar to PET/CT for the diagnosis of more than 16 different neoplastic lesions. However, at present, the literature still supports PET/ CT as a main player in the diagnosis and staging of gastric cancer [9][10][11], and PET/MRI has rarely been reported as being used in the study of gastric tumors, which is partially because of the confounding effects from respiratory movements, gastrointestinal peristalsis and cardiac pulsation on MRI. Nevertheless, driven by the appealing merits of high soft tissue contract and no ionizing radiation, MRI is widely used in abdominal imaging.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review by Riola-Parada et al [8] showed that PET/MRI was superior or similar to PET/CT for the diagnosis of more than 16 different neoplastic lesions. However, at present, the literature still supports PET/ CT as a main player in the diagnosis and staging of gastric cancer [9][10][11], and PET/MRI has rarely been reported as being used in the study of gastric tumors, which is partially because of the confounding effects from respiratory movements, gastrointestinal peristalsis and cardiac pulsation on MRI. Nevertheless, driven by the appealing merits of high soft tissue contract and no ionizing radiation, MRI is widely used in abdominal imaging.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to CT, PET has better performance, which means metabolic parameters play an important role in the model. The most commonly used metabolic parameter of PET/CT is SUVmax, which indicates the additional value of predicting metastasis and prognosis ( 44 , 45 ). In addition, CA125 is one of the clinically promising diagnostic markers in evaluating the efficacy of chemotherapy and predicting the prognosis of patients with peritoneal dissemination ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous report identified that (F-18)FLT-PET/CT, despite low SUV, has a higher sensitivity than FDG-PET in GC, regardless of the histological type [65,66]. Honma et al [67], in a proof-of-concept study, explored the sensitivity of 18F-fluothymine (F-18)FLT PET/CT for detecting PM from GC previously identified by other imaging mo- A recent paper evaluated the value of FDG PET/MRI for assessing the extent of peritoneal metastases in 34 patients with ovarian and endometrial cancer [64]. They found a close correlation between PCI evaluation using PET/MRI, DW-MRI alone, and surgery.…”
Section: Novel Pet Radiotracersmentioning
confidence: 99%
“…A previous report identified that (F-18)FLT-PET/CT, despite low SUV, has a higher sensitivity than FDG-PET in GC, regardless of the histological type [65,66]. Honma et al [67], in a proof-of-concept study, explored the sensitivity of 18F-fluothymine (F-18)FLT PET/CT for detecting PM from GC previously identified by other imaging modalities. A total of 19 patients, including 15 patients with diffuse-type, were analysed.…”
Section: Novel Pet Radiotracersmentioning
confidence: 99%